2011
DOI: 10.1007/s11064-011-0632-x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Cerebellum Redox States and Cholinergic Functions Contribute to the Beneficial Effects of Silymarin Against Manganese-Induced Neurotoxicity

Abstract: Manganese (Mn) is a potent neurotoxin involved in the initiation and progression of various cognitive disorders. Oxidative stress is reported as one of accepted mechanisms of Mn toxicity. The present study was designed to explore the effects of silymarin, a natural antioxidant, in attenuating the toxicity induced by Mn in rat cerebellum. In this investigation, rats were treated orally with MnCl₂ (20 mg/ml) for 30 days, subsets of these animals were treated intraperitoneally daily with silymarin (100 mg/kg) alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 51 publications
(49 reference statements)
1
26
0
5
Order By: Relevance
“…The doses of silymarin and the course for 5 consecutive days for DMSA were based on the previous reports. 24,25 We found that Pb exposition caused a significant increase in the BLLs compared with the control group. DMSA administration caused a significant decrease in BLLs.…”
Section: Discussionmentioning
confidence: 72%
“…The doses of silymarin and the course for 5 consecutive days for DMSA were based on the previous reports. 24,25 We found that Pb exposition caused a significant increase in the BLLs compared with the control group. DMSA administration caused a significant decrease in BLLs.…”
Section: Discussionmentioning
confidence: 72%
“…6I), is a site of significant lipopigment accumulation at 52 weeks of age in CLN6 mice (Thelen et al, 2012b). Moreover, Purkinje cell loss was reported to be an early pathological feature in mouse models of infantile, late infantile and juvenile NCL diseases (Sleat et al, 2004; Macauley et al, 2009; Weimer et al, 2009), and oral treatment of rats with manganese for 30 days resulted in cerebellar Purkinje cell loss and morphological abnormalities (Chtourou et al, 2012). Importantly, Purkinje cells are essential for controlling motor and learning functions, and motor symptoms were the first to be detected in this model (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, crude aqueous extracts of Melissa officinalis blunted the Mn-induced striatal and hippocampal lipid peroxidation [187]. Purified flavonoids, such as, silymarin (obtained from Silybum marianum , a plant with hepatoprotecive properties) protected neuroblastoma cells [188] and prevented Mn-induced oxidative stress in brain, liver, and kidney of rats [189191]. Lycopene has also been reported to decrease the neurotoxicity of Mn in rats [192].…”
Section: Main Textmentioning
confidence: 99%